Atractylenolide-1 Targets FLT3 to Regulate PI3K/AKT/HIF1-α Pathway to Inhibit Osteogenic Differentiation of Human Valve Interstitial Cells - Wang, Jie; Zhang, Penghua; Zhang, Jing; Ma, Zhaohui; Tian, Xingqin; Liu, Yan; Lv, Guanghui; Qu, Linghang (Frontiers in Pharmacology, 2022)
Atractylenolide-1 (AT-1), a natural active ingredient extracted from Atractylodes macrocephala, was reported to have good anti-fibrotic and anti-inflammatory effects. Osteogenic changes induced by the inflammation of valve interstitial cells (VICs) play a role in the development of calcified aortic valve disease (CAVD). This study aimed to investigate the anti-osteogenic effects of AT-1 in human VICs. Human VICs were exposed to osteogenic induction medium (OM) containing AT-1 to analyze cell viability, as well as protein and osteogenic gene expression. Anti-calcification tests were also performed. mRNA transcriptome sequencing was performed to identify differential genes and pathways regulated by AT-1. Western blotting was used to verify the enrichment pathway, protein-protein interaction (PPI) analysis was conducted to identify drug targets. Finally, molecular docking and inhibitors are used to verify the drug targets. Treatment of VICs with 20 μM AT-1 resulted in no significant cytotoxicity. The addition of AT-1 to OM prevented the accumulation of calcified nodules, and decreases in the level of (Alkaline Phosphatase) ALP and RUNX2 gene and protein expression were observed. Atractylenolide-1 can target FLT3 protein and inhibit the phosphorylation of FLT3, thereby blocking PI3K/AKT pathway activation, reducing the production of Hypoxia inducible factor(HIF)1-α, and inhibiting the osteogenic differentiation of VICs. These results suggest AT-1 as a potential drug for treating calcified aortic valve disease.